Najarula saṅga o prasaṅga - Bhattacharya, Gauri Shankar, 1921- (Amara Sāhitya Prakāśana, 1977)
Collection of writings on the life and works of the Bengali poet and revolutionary Kazi Nazrul Islam, 1899-1976, by close associates of the poet and Bengali litterateurs.